2022
DOI: 10.3389/fpubh.2022.926819
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Body Composition Estimated by Air-Displacement Plethysmography in Chinese Preschool Children

Abstract: ObjectiveTo describe the characteristics of body composition by air-displacement plethysmography (ADP) among Chinese preschool children.MethodsPreschool children were recruited from three kindergartens. Adiposity indices were evaluated using the ADP method. BMI, fat mass index (FMI), fat-free mass index (FFMI) and waist-to-height ratio (WHtR) were calculated. Overweight and obesity were diagnosed using the WHO reference. Analyses were executed by SPSS and MedCalc software. Smoothed curves were constructed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In the present study, we have shown that the values of these indexes in boys and girls significantly decrease at the age of 3–5 years, which is consistent with the results of a previous analysis of the body composition of 3,593 healthy individuals aged 4–24 years in Germany [ 28 ]. Besides, data from 1011 children aged 3–5 years old in Tianjin [ 11 ], And research of 1243 preschool children in Xiamen, China [ 29 ], also showed declining trend of FMI, and FM% among both boys and girls. Thus, it appears that there are similarities in the changes of body fat percentage in different regions, countries and ethnicities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we have shown that the values of these indexes in boys and girls significantly decrease at the age of 3–5 years, which is consistent with the results of a previous analysis of the body composition of 3,593 healthy individuals aged 4–24 years in Germany [ 28 ]. Besides, data from 1011 children aged 3–5 years old in Tianjin [ 11 ], And research of 1243 preschool children in Xiamen, China [ 29 ], also showed declining trend of FMI, and FM% among both boys and girls. Thus, it appears that there are similarities in the changes of body fat percentage in different regions, countries and ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Fangfang Chen performed the research among 3- to 5-year-old children in Tianjin, China [ 11 ]. Ling Bai reported the results of body composition using the BIA in Chinese children (10–18 years old), mainly focus the attention on the associations of body fat distribution and lean body mass with blood pressure in normal-weight children and adolescents [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…BOD POD ® is a commercially available ADP instrument for assessing body composition that is used in clinical, commercial, and research settings ( 16 ). ADP offers a fast, accurate, and reliable means of assessing body composition in children ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under the assumption that whole-body BMD between vegans and RMEs was 0.06 g/cm 2 (a significant difference in clinical relevance) and given that the between-subject standard deviation (SD) on whole-body BMD is 0.10 g/cm 2 , we estimated that a sample size of 45 individuals per dietary pattern group was required to have a power of 80% to detect differences (Cohen's D 0.6 SD) between groups at the confidence interval of 95% (49). Significant variables (p < 0.05), along with those deemed important based on expert opinion and literature, were considered potential confounding variables in regression models (50). Since BMI was identified as an important mediator and not a confounder, a seemingly unrelated linear regression model was employed for each outcome, treating dietary patterns as the exposure factor and incorporating the relevant potential confounding variables as covariates (age, sex, physical activity, duration of dietary pattern, height, alcohol intake, calcium and/or vitamin D supplements, and level of education) and BMI as a mediator (50,51).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Significant variables (p < 0.05), along with those deemed important based on expert opinion and literature, were considered potential confounding variables in regression models (50). Since BMI was identified as an important mediator and not a confounder, a seemingly unrelated linear regression model was employed for each outcome, treating dietary patterns as the exposure factor and incorporating the relevant potential confounding variables as covariates (age, sex, physical activity, duration of dietary pattern, height, alcohol intake, calcium and/or vitamin D supplements, and level of education) and BMI as a mediator (50,51). Bonferroni corrected alpha 0.0008 (n = 64 tests) reports the comparison between the P < 0.0008 and those where P < 0.05 since this is an exploratory study aiming to minimize type 2 errors.…”
Section: Statistical Analysesmentioning
confidence: 99%